Dairy Cow Longevity Is Affected by Dam Parity and Age - Bobadilla PE; López-Villalobos N; Sotelo F; Damián JP (MDPI (Basel, Switzerland), 2024)
The objective of this study was to determine whether the parity and age of dams affect the longevity of their offspring in dairy cows in pasture-based systems. A total of 12,792 dairy cows born between 2000 and 2017 across five farms were evaluated using records from the Dairy Herd Improvement Database at Instituto Nacional para el Control y Mejoramiento Lechero (Uruguay). Dams were classified as primiparous or multiparous, and parity number and age were considered. The effect of parity status on herd life (HL), the length of productive life (LPL), and the productive life index (PLI) was evaluated using a generalized mixed model. Associations between parity number and dam age with HL, LPL, and PLI were evaluated using regression models. HL, LPL, and PLI were significantly higher for daughters of multiparous cows. Dams with more parities gave birth to longer-living daughters, with an average HL difference of 4.4 months between the first and seventh parity of the dams. The parity number and age of the dam showed a significant association with HL, LPL, and PLI. In conclusion, the parity and age of the dam influence the longevity of dairy cows in pasture-based systems, with older dams and higher parity yielding daughters with greater longevity.
Keywords: herd life; length of productive life; pasture-based production